Fragmented habitats of traditional fruit orchards are important for dead wood-dependent beetles associated with open canopy deciduous woodlands - Horak, Jakub (Die Naturwissenschaften, 2014)
The conservation of traditional fruit orchards might be considered to be a fashion, and many people might find it difficult to accept that these artificial habitats can be significant for overall biodiversity. The main aim of this study was to identify possible roles of traditional fruit orchards for dead wood-dependent (saproxylic) beetles. The study was performed in the Central European landscape in the Czech Republic, which was historically covered by lowland sparse deciduous woodlands. Window traps were used to catch saproxylic beetles in 25 traditional fruit orchards. The species richness, as one of the best indicators of biodiversity, was positively driven by very high canopy openness and the rising proportion of deciduous woodlands in the matrix of the surrounding landscape. Due to the disappearance of natural and semi-natural habitats (i.e., sparse deciduous woodlands) of saproxylic beetles, orchards might complement the functions of suitable habitat fragments as the last biotic islands in the matrix of the cultural Central European landscape.
Keywords: brouci; Biodiversity; Animals; zachování přírodních zdrojů; zvířata; ekosystém; stromy; Coleoptera; Ecosystem; Czech Republic; Trees; Wood; biodiverzita; Conservation of Natural Resources; dřevo; Česká republika